Cultivating Change: A Community-driven Approach to Organic Waste in Padukuhan Nglebeng - Tiaranty Esperansa Situmorang; Andika; Yusa Putra Widyatama; Boby Prayoga; Kiki Sarnita; Lula Annisa; Maiken Des Riu; Nur Faidzin; Raka Juniar Renaldy; Sindy; Talabu Karyaman Tuyamaku Buulolo (PT Inovasi Pratama Internasional, 2023)
Household waste is the main contributor to organic waste. Improper management of organic waste can have negative environmental consequences. In Padukuhan Nglebeng, the lack of knowledge among the community, especially housewives, about the dangers and benefits of household waste has led to the accumulation of unprocessed waste in disposal sites. To address this issue, an outreach program was conducted, focusing on enhancing the community's understanding and awareness of the environmental impact of organic waste. The program included four stages: observation, socialization, practical application, and evaluation. Initially, the participants had limited knowledge about organic waste, scoring an average of 63% in the